Plan de negocio para la creación de una microempresa dedicada al servicio de limpieza doméstica en la ciudad de Quevedo, año 2012 - Floril Lara, Jorge Fabián (2013)
The business activity is to provide a domestic cleaning service with added value; this will need to create a small business under the administrative guidelines that establish a management model for meeting the objectives. The vision is to achieve in the medium term a level of competitiveness and positioning with the cleaning service between the main city of Quevedo, so get achieve sustained and sustainable growth of the business that allows us to absorb a significant percentage in the local market. The mission to be a company that provides housekeeping and maintenance of homes, whose task is to ensure our customers a high quality service through a strategic location, adequate infrastructure, competitive prices and excellent customer service, demonstrating the commitment and concern for their property to contribute to maximum operational life and property. Taking into account an environmental management system, minimizing the impact of pollution. Microenterprise clients are the economically active population of the city of Quevedo, seeking an efficient and guaranteed to maintaining and cleaning your home or workspace. The needs of our customers are getting an excellent service and quality, which is within reach of their pockets. Our competitive advantage will provide guarantee for our work especially when it comes to deep cleaning. In the market investigation it was determined that Quevedo is an attractive place for this type of business, as it has not been exploited